2017
DOI: 10.1007/978-94-024-1079-2_50
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Xylose-Taurine Reduced against Damages Caused by Oxidative Stress in Zebrafish Embryos In Vivo Model

Abstract: The zebrafish (Danio rerio) is useful and convenient vertebrate models in various studies in human disease and drug discovery. In this present study, we first evaluated whether Xylose-Taurine reduced (X-T-R), a taurine derivate protects zebrafish embryos against oxidative stress caused by AAPH (2,2'-Azobis(2-amidinopropane) dihydrochloride). First of all, we selected the concentration of X-T-R showing no toxicity in zebrafish embryos. We identified that X-T-R significantly increased the survival of zebrafish e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…In our study, we confirmed that hepatic antioxidant enzyme activities such as those of GSH-Px, SOD, and CAT were markedly increased in both T-X-and DS-treated rats compared to those in the CON group. In a previous study, we confirmed that xylose-taurine-reduced (X-T-R), a taurine derivate, improved the survival rate of zebrafish embryos by suppressing intracellular NO and ROS generation 35 . X-T-R also showed potent hepatoprotective effects against oxidative damage induced by hydrogen peroxide in response to Nrf2 signaling 36 .…”
Section: Discussionsupporting
confidence: 54%
“…In our study, we confirmed that hepatic antioxidant enzyme activities such as those of GSH-Px, SOD, and CAT were markedly increased in both T-X-and DS-treated rats compared to those in the CON group. In a previous study, we confirmed that xylose-taurine-reduced (X-T-R), a taurine derivate, improved the survival rate of zebrafish embryos by suppressing intracellular NO and ROS generation 35 . X-T-R also showed potent hepatoprotective effects against oxidative damage induced by hydrogen peroxide in response to Nrf2 signaling 36 .…”
Section: Discussionsupporting
confidence: 54%